Understanding movie streaming websites in Indonesia as unlimited movie access in the digital era - Wibowo, Tangguh Okta (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study was aimed to explore the issue of watching movies through movie streaming website in Indonesia. The presence of internet technology in the digital era has transformed the practice of watching movies that can now be accessed anywhere and anytime through more practical devices (mobile). It brings up two dispute sides, hacktivist movement (left side, seen as illegal) and movie industries and government (right side), and the internet opens this new ‘war’. The internet has changed the physical distribution and enabled an efficient content distribution through peer-to-peer. The movie streaming website enables viewers to accessvia streaming all movies stored in cloud storage and they can also download them freely to their computer. This study also highlights the streaming movie website as a promising business. It converts the web traffic to ads for impression and clicks for generating a revenue. In the final section, this article highlights the activities of the other side to avoid the deterministic perceptions that perceive as mere hijacking acts and consider the future of movie-watching practices in the digital era with the presence of various streaming media, such as Netflix, Iflix, Viu, Mox and Genflix. The research findings show that the dispute of watching movies online brings the complexity and rivalry between government and the website owner.